Electromyographic analysis of the masseter and buccinator muscles with the pro-fono facial exerciser use in bruxers - Jardini, Renata S. R.; Ruiz, Lydia S. R. [UNESP]; Moysés, Maria A. A. (Taylor & Francis, 2006)
The aim of this study was to evaluate the efficiency of the Pró-Fono Facial Exerciser (Pró-Fono Productos Especializados para Fonoaudiologia Ltda., Barueri/SP, Brazil) to decrease bruxism, as well as the correlation between the masseter and the buccinator muscles using electromyography (EMG). In this study, 39 individuals ranging from 23 to 48 years of age were selected from a dental school and then underwent surface EMG at three different periods of time: 0, 10, and 70 days. They were divided into a normal control group, a bruxer control group (without device), and an experimental bruxer group who used the device. The bruxer group showed a greater masseter EMG amplitude when compared to the normal group, while the experimental group had deceased activity with a reduction in symptoms. The buccinator EMG spectral analysis of the experimental bruxist group showed asynchronous contractions of the masseter muscle (during jaw opening) after using the Pró-Fono Facial Exerciser. The normal group also showed asynchronous contractions. Upon correlation of the data between these muscles, the inference is that there is a reduction in bruxism when activating the buccinator muscle. Copyright © 2006 by CHROMA, Inc.